Functions of Representative Speech: Analysis of The Status on Facebook Social Media - Marzuki, Ismail (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2022)
This study aims to describe the functions of representative speech used by users of the social media application Facebook. The study uses a descriptive qualitative method, and data is collected through documentation techniques from the social media platform Facebook. The data analyzed in this study includes words, sentences, and paragraphs posted by Facebook users. The results of this study reveal that representative speech has four functions: (1) to state the hopes, principles, aspirations, and beliefs of the speaker, (2) to inform readers or interlocutors about information, events, concepts, and knowledge, (3) to suggest that interlocutors believe, do, or follow something that the speaker has experienced, and (4) to complain about what the speaker is feeling, thinking, or doing and hoping to receive comments, approval, and feedback from interlocutors. This research is relevant to the study of language acts and representative speech on the Facebook social media platform.